If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + 2)(X + 3) = 30 Reorder the terms: (2 + X)(X + 3) = 30 Reorder the terms: (2 + X)(3 + X) = 30 Multiply (2 + X) * (3 + X) (2(3 + X) + X(3 + X)) = 30 ((3 * 2 + X * 2) + X(3 + X)) = 30 ((6 + 2X) + X(3 + X)) = 30 (6 + 2X + (3 * X + X * X)) = 30 (6 + 2X + (3X + X2)) = 30 Combine like terms: 2X + 3X = 5X (6 + 5X + X2) = 30 Solving 6 + 5X + X2 = 30 Solving for variable 'X'. Reorder the terms: 6 + -30 + 5X + X2 = 30 + -30 Combine like terms: 6 + -30 = -24 -24 + 5X + X2 = 30 + -30 Combine like terms: 30 + -30 = 0 -24 + 5X + X2 = 0 Factor a trinomial. (-8 + -1X)(3 + -1X) = 0Subproblem 1
Set the factor '(-8 + -1X)' equal to zero and attempt to solve: Simplifying -8 + -1X = 0 Solving -8 + -1X = 0 Move all terms containing X to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1X = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1X = 0 + 8 -1X = 0 + 8 Combine like terms: 0 + 8 = 8 -1X = 8 Divide each side by '-1'. X = -8 Simplifying X = -8Subproblem 2
Set the factor '(3 + -1X)' equal to zero and attempt to solve: Simplifying 3 + -1X = 0 Solving 3 + -1X = 0 Move all terms containing X to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1X = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1X = 0 + -3 -1X = 0 + -3 Combine like terms: 0 + -3 = -3 -1X = -3 Divide each side by '-1'. X = 3 Simplifying X = 3Solution
X = {-8, 3}
| L^2+6L-160=0 | | 3x+5=8x-13 | | 3y-5x=43 | | abs(z+4)=3*abs(z-4) | | 16+9t=22 | | 2x-8+3x+21=3 | | 16a-9a+uf= | | 50y+3y=513 | | 3x+20+2x+40=180 | | 24-10n=18 | | (3x-1)+(2x+4)= | | 12x-6=14x+35 | | 6t-2=5t+134 | | -2(4y+15)+8y=5 | | c+c+2c+5+4= | | 2(-2)-y=1 | | 5x-3(2x-1)=5 | | -43-14y+13=-32y+14+7y | | 7y+1=9+3 | | -8v+18=2(v+4) | | 2x^2-2015x+2015=0 | | n(x)=0 | | -7u+3(u-7)=7 | | 3(v+2)+2v=-14 | | (13+2x)-(4-x)= | | 7xln(x)=0 | | 21-y=6 | | 3x(8y-5)= | | -44-8y+14=-21y+45+8 | | (3x-1)x=4 | | 10+2=2 | | 5.345x-x=50 |